International Conference on Space Optics — ICSO 2012 2017
DOI: 10.1117/12.2309048
|View full text |Cite
|
Sign up to set email alerts
|

Taranis MCP: a joint instrument for accurate monitoring of transient luminous event in the upper atmosphere

Abstract: Abstract-The TARANIS microsatellite -CNES, Myriade family -is dedicated to the study of the impulsive transfers of energy between the Earth atmosphere and the space environment, including transient phenomena such as Transient Luminous Events (TLEs) and Terrestrial Gamma-ray Flashes (TGFs). It observes from above thunderstorm areas. Part of the payload, the "MicroCameras and Photometers" (MCP) instrument is in charge of the remote sensing of TLEs in terms of optical imaging and waveforms. Its objectives are to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The image subtraction procedure is first proposed by Blanc et al []. More recently, Blanc et al [] first suggested the subtraction of images to detect TLEs in nadir images taken by two cameras having a similar configuration. We use basically the same image subtraction procedure.…”
Section: Methodology Of Data Processingmentioning
confidence: 99%
“…The image subtraction procedure is first proposed by Blanc et al []. More recently, Blanc et al [] first suggested the subtraction of images to detect TLEs in nadir images taken by two cameras having a similar configuration. We use basically the same image subtraction procedure.…”
Section: Methodology Of Data Processingmentioning
confidence: 99%
“…Since the Summer of 2017, the software FreeTure contains an experimental realtime algorithm for the detection of TLEs. This algorithm runs along with the meteor detection part on selected stations with a view to help localize TLEs observed by the future CNES space mission TARANIS (Blanc et al 2017). The FRIPON network infrastructure can also be used to conduct large-scale light pollution monitoring campaigns using the all-sky calibration images collected over time (Jechow et al 2018).…”
Section: Other Recordsmentioning
confidence: 99%
“…For this reason, a subtraction of the appropriately scaled LSI-1 image from the LSI-2 image is required to extract only the TLE emissions (Sato et al 2015). The image subtraction acquired by two cameras having a similar configuration was first proposed by Blanc et al (2004Blanc et al ( , 2012. We basically used the same subtraction scheme.…”
Section: Image Subtraction Methods For Lsi Datamentioning
confidence: 99%